Antimalarial activity of root extract of Tephrosia villosa L. Pers. (Fabaceae) on Plasmodium berghei-infected mice - Muluken Adela Alemu; Tilaye Arega Moges; Tirsit Ketsela Zeleke; Rahel Belete Abebe; Woretaw Sisay Zewdu (Scientific Reports)
Abstract Scientists are urged to discover new drugs since treatment resistance makes malaria hard to control. One important source of new drugs is medicinal plants. The antimalarial qualities of Tephrosia villosa roots in vitro demonstrated its good effect to treat malaria infections. On the other hand, its effect in vivo is unknown. This study filled the gap by evaluating the antimalarial effectiveness of Tephrosia villosa’s Dichloromethane/methanol (1:1) extract against Plasmodium berghei infection in a mouse model.Dichloromethane/methanol (1:1) was used to extract the dried, powdered roots of Tephrosia villosa, and the extract’s safety profile was assessed using an acute toxicity test. By giving 100, 200, and 400 mg/kg dosages of the extract, the antimalarial activity of the extract was assessed by the 4-day suppressive, Rane’s, and prophylactic tests. To establish the activity, criteria such as body weight, packed cell capacity, temperature, survival time, and parasitemia level were measured.According to the acute oral toxicity result, the extract caused no signs of toxicity in mice in 24 h and within 14 days of observation. It was proven to have chemosuppressive, curative, and prophylactic activities. It has decreased the level of parasitemia and improved mean survival time in parasite infected mice in used models. The extract at 400 mg/kg dose suppressed parasitemia by 24.78%, 52.16%, and 49.09% in 4-day suppressive, curative and prophylactic test models (p < 0.001) respectively. Moreover, it inhibited reduction in packed cell volume, body weight, and temperature fall in all tested models as compared to the negative control. The findings revealed that the extract of the plant was safe at 2 g/kg dose on acute oral toxicity test and was proven to have antimalarial effect for plasmodium berghei infection in mice which supports the in vitro test.